A Review on Mitigation Technologies for Controlling Urban Heat Island Effect in Housing and Settlement Areas. (May 2018) - Andoni, Heri; Wonorahardjo, Surjamanto
Abstract: Urban Heat Island (UHI) has many harm impacts to urban and human life, the examples are increased building and energy consumption, increased air pollutants emissions, compromised human comfort and health, and many more. Despite UHI phenomenon and those impacts has been realized long enough by the experts along with development of major cities in the world, but its mitigation technology has not been well developed. This paper discusses few mitigation technologies for UHI phenomenon that have been developed by experts. Some mitigation technologies such as double skin façade, shading strategies, and many more are discussed in this study, include the strengths and the weaknesses of each strategy. The focus of the study is mainly on the potential of building skin engineering in which thermal conductivity, infrared emissivity, and specific heat factors. The selected case discussed are buildings made of heavy weight materials. The result in this study reveals a potential map where thermal insulation is one potential strategy to reduce the intensity of UHI through the reduction of heat emissions of heavy building materials components. By this study, improvement of the urban life in its relation to UHI are expected to occur, especially in housing and settlements area.